2013
DOI: 10.1002/ijc.28514
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory variation in the performance of liquid-based cytology: Insights from the ATHENA trial

Abstract: Although it is recognized that cervical cytology is highly subjective, and that there is considerable interlaboratory variation in how slides are evaluated, little is known as to how this impacts the performance of cytology. In the ATHENA trial, liquid-based cytology specimens from 46,887 eligible women !21 years of age were evaluated at four large regional US laboratories, providing a unique opportunity to evaluate the impact of interlaboratory variations on the performance of cervical cytology. All women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 23 publications
3
75
1
2
Order By: Relevance
“…El material obtenido se conserva inmediatamente tras su extracción en un medio líquido, normalmente de base alcohólica, que permite su almacenaje y transporte, y la extensión se realiza en el laboratorio. Los estudios publicados, incluyendo un metaanálisis, coinciden en que este tipo de citología disminuye los casos inadecuados para diagnóstico, en los que hay que repetir la toma de la muestra, acorta el tiempo de lectura al microscopio y ofrece un discreto aumento de la sensibilidad [76][77][78][79][80][81][82][83][84][85] . Un valor añadido de la citología en medio líquido es que no se utiliza todo el material para realizar el estudio citológico, y el material remanente conservado en el líquido de fijación durante semanas a temperatura ambiente permite realizar técnicas adicionales, moleculares como la determinación de VPH, o de inmunocitoquímica, como la detección de p16/KI67, o futuros nuevos marcadores, evitando así una nueva toma y, por tanto, una visita de la paciente, factor que debe tenerse en cuenta en el cálculo de coste-efectividad de esta técnica 79 .…”
Section: Citología En Medio Líquidounclassified
“…El material obtenido se conserva inmediatamente tras su extracción en un medio líquido, normalmente de base alcohólica, que permite su almacenaje y transporte, y la extensión se realiza en el laboratorio. Los estudios publicados, incluyendo un metaanálisis, coinciden en que este tipo de citología disminuye los casos inadecuados para diagnóstico, en los que hay que repetir la toma de la muestra, acorta el tiempo de lectura al microscopio y ofrece un discreto aumento de la sensibilidad [76][77][78][79][80][81][82][83][84][85] . Un valor añadido de la citología en medio líquido es que no se utiliza todo el material para realizar el estudio citológico, y el material remanente conservado en el líquido de fijación durante semanas a temperatura ambiente permite realizar técnicas adicionales, moleculares como la determinación de VPH, o de inmunocitoquímica, como la detección de p16/KI67, o futuros nuevos marcadores, evitando así una nueva toma y, por tanto, una visita de la paciente, factor que debe tenerse en cuenta en el cálculo de coste-efectividad de esta técnica 79 .…”
Section: Citología En Medio Líquidounclassified
“…Kaiser Permanente Northern California reported follow-up data on 11 The United States ATHENA (Addressing the Need for Advanced HPV Diagnostics) trial reported Roche cobas HPV rates. 12 Among 45 933 women aged 21 years or older undergoing routine cervical cancer screening, prevalence of HR-HPV (14 genotypes), HPV16, and HPV18 was 12.5%, 2.8%, and 1.0%, respectively, and the presence of HPV16 was the most important risk factor for CIN. The overall prevalence of HR-HPV for women with negative Pap test results was 9.8%, 12 lower than the results of our study, which showed positive results in approximately one-fifth of women with negative Pap test results (Table 7).…”
Section: Ofmentioning
confidence: 99%
“…12 Among 45 933 women aged 21 years or older undergoing routine cervical cancer screening, prevalence of HR-HPV (14 genotypes), HPV16, and HPV18 was 12.5%, 2.8%, and 1.0%, respectively, and the presence of HPV16 was the most important risk factor for CIN. The overall prevalence of HR-HPV for women with negative Pap test results was 9.8%, 12 lower than the results of our study, which showed positive results in approximately one-fifth of women with negative Pap test results (Table 7). Among the 32 260 women aged 30 years or older with a negative Pap test result, the overall prevalence of HR-HPV detected with the cobas HPV Test was 6.7% and the overall prevalence rates for HPV16, HPV18, and 12 other HR-HPV genotypes were 1.0%, 0.5%, and 5.2%, respectively.…”
Section: Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Furthermore, data on the ASC/squamous intraepithelial lesion ratios of these laboratories place them in a laboratory performance category linked to suboptimal screening sensitivity. [14] Performance of these four US cytology laboratories[15] appears particularly suboptimal when compared to the performance of United Kingdom (UK) laboratories competing against hybrid capture two HPV testing in the first two rounds of the ARTISTIC trial. [16] The performance of the UK LBC laboratories was so strong that the UK investigators commented: “It is difficult to escape the conclusion that LBC was more sensitive in ARTISTIC than earlier conventional cytology”.…”
mentioning
confidence: 99%